Chemical Composition, Fatty Acids Content and Glycemic Index of Two Different Types of Omani Halwa - Ali, Amanat; Al-Zuhaibi, Khalid M.; Waly, Mostafa I.; Al-Alawi, Ahmed A.; Al-Sabahi, Jamal N.; Sankar, Devarajan (Pakistan Journal of Nutrition, 2013)
The study evaluated the chemical composition, fatty acids contents and Glycemic Index (GI) of two different types (white and black) of Omani halwa. Representative samples of Omani halwa were collected from the local market. The proximate composition and energy contents of white and black halwa did not vary significantly (p<0.05). The percentage moisture, crude protein, total fat, ash, crude fiber and Nitrogen Free Extract (NFE) in white and black halwa were 11.8 and 12.1; 0.28 and 0.44; 13.8 and 12.4; 0.01 and 0.02; 0.15 and 0.05 and 74.0 and 75.0, respectively. The energy values in white and black halwa were 421.3 and 413.4 kcal/100 g, respectively. No significant (p<0.05) differences were observed in the total fatty acids, Saturated Fatty Acids (SFA), Monounsaturated Fatty Acids (MUFA) and Polyunsaturated Fatty Acids (PUFA) content in both types of Omani halwa. The SFA were present in highest concentration. The proportionate percentages of SFA, MUFA and PUFA in white and black halwa were 64.57, 65.47, 31.28, 30.79, 4.11 and 3.74%, respectively. The average GI and GL values for white and black halwa also did not vary (p<0.05) and were 54.8 and 52.0 and 14 and 13.4, respectively. Although the glycemic index values of Omani halwa fall in low GI category (<55), it should be consumed with caution because of its high fat, in particular of SFA and high sugar contents.